Risk factors for heparin-induced thrombocytopenia: Focus on Fcγ receptors - Rollin, Jérôme; Pouplard, Claire; Gruel, Yves (Thrombosis and Haemostasis, 2016)
Fcγ receptors have critical roles in the pathophysiology of heparin-induced thrombocytopenia (HIT), a severe immune-mediated complication of heparin treatment. Activation of platelets, monocytes and neutrophils by platelet-activating anti-PF4/heparin IgG antibodies results in thrombocytopenia, hypercoagulability and thrombosis in susceptible patients, effects that depend on FcγRIIA. In addition, FcγRIIIA receptors probably contribute to clearance of platelets sensitised by HIT immune complexes. FcγRI has also been reported to be involved in monocyte activation by HIT IgG antibodies and synthesis of tissue factor. This review focuses on the role of these FcγRs in HIT pathophysiology, including the potential influence of several gene variations associated with variable risk of HIT and related thrombosis. In particular, the 276P and 326Q alleles of CD148, a protein tyrosine phosphatase that regulates FcγRIIA signalling, are associated with a lower risk of HIT, and platelets from healthy donors expressing these alleles are hyporesponsive to anti-PF4/H antibodies. It was also recently demonstrated that the risk of thrombosis is higher in HIT patients expressing the R isoform of the FcγRIIA H131R polymorphism, with HIT antibodies shown to activate RR platelets more efficiently, mainly explained by an inhibitory effect of normal IgG2, which bound to the FcγRIIA 131H isoform more efficiently. Environmental risk factors probably interact with these gene polymorphisms affecting FcγRs, thereby increasing thrombosis risk in HIT.
Keywords: Heparin; thrombocytopenia; Fcγ receptors; gene polymorphisms